Application of Black Scholes Method for Determining Agricultural Insurance Premiums Based on the Rainfall Index Using the Historical Burn Analysis Method - Zahra, Ami Emelia Putri; Riaman, Riaman; Sukono, Sukono (iora, 2023)
Indonesia is a tropical area where it often rains. Uncertain rainfall conditions can have an impact in the form of losses in agriculture, including for rice farmers. The total rice productivity in Indonesia, one of which is in Majalengka Regency, is thought to be quite high, so the losses will be significant. Therefore, it is necessary to make efforts to reduce the impact of losses experienced by farmers, one of which is through insurance programs in the agricultural sector. Rainfall index-based agricultural insurance provides protection to farmers in the form of capital assistance in the event of crop damage resulting in crop failure due to erratic rainfall. This study aims to calculate the agricultural insurance premium based on the rainfall index. The method used to calculate the premium is the Black-Scholes method, while the Historical Burn Analysis method is used to determine the rainfall index. The data used is rainfall data in Majalengka Regency in 2014–2021. The results showed that the premium price in Majalengka Regency depends on the value of the trigger obtained, with a price range between IDR 1,089,646.39 and IDR 1,266,213.02.